2014
DOI: 10.1080/02763893.2013.858092
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and Control in Everyday Life in Care of Older People in Nursing Homes

Abstract: Self-control and autonomy are not guaranteed when people age and are in need of help from others, especially in institution-based housing. This occurs despite the fact that it is a generally accepted belief that care should be delivered with the greatest possible degree of independence and autonomy. This article discusses older people's experiences with and the opportunities for autonomy in institution-based housing. Through focus group interviews and observations, the daily lives of residents at two nursing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 47 publications
1
55
0
1
Order By: Relevance
“…Certainly, the rights discourse fits with the revised 2014 Declaration of Sexual Rights by the World Association for Sexual Health, which states that 'sexuality is grounded in universal human rights', and 'is a central aspect of being human throughout life'. The findings in this study of different discourses shaping staff and community understandings about sexual expression and intimacy are consistent with the nascent body of knowledge about the polemic in aged care between privacy and protection (Bauer, 1999;Cornelison & Doll, 2013;Doyle, 2014;Frankowski & Clark, 2009;Morgan, 2009;Reingold & Burros, 2004;Wikström & Emilsson, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Certainly, the rights discourse fits with the revised 2014 Declaration of Sexual Rights by the World Association for Sexual Health, which states that 'sexuality is grounded in universal human rights', and 'is a central aspect of being human throughout life'. The findings in this study of different discourses shaping staff and community understandings about sexual expression and intimacy are consistent with the nascent body of knowledge about the polemic in aged care between privacy and protection (Bauer, 1999;Cornelison & Doll, 2013;Doyle, 2014;Frankowski & Clark, 2009;Morgan, 2009;Reingold & Burros, 2004;Wikström & Emilsson, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…For example, a study of two Swedish nursing homes found the sector's ambivalent mission as a place of care and a place of residence compromised residents' autonomy (Wikström & Emilsson, 2014). A study of three assisted living settings in the US found that matters of sexual expression were further confounded by ambiguity about who the rightful client and primary decision-maker is, and at what point a resident's cognitive decline impinges on their capacity to make competent decisions (Frankowski & Clark, 2009).…”
Section: Privacy Protection and Power Dynamics In Aged Carementioning
confidence: 98%
“…The power shift is central in the Swedish Patient Act (Patientlag, 2014) and in the literature on patient participation (Sahlsten et al, 2008 (Halskov et al, 2017). There is a risk of dehumanization when professionals think that older persons are too ill to participate (Wikström & Emilsson, 2014) or suffer from cognitive impairment and are not able to make decisions and therefore not involved in their care (Poulos et al, 2017). However, even older persons with dementia might be able to participate since their capacity for decision-making varies from day to day ().…”
Section: Discussionmentioning
confidence: 99%
“…Nursing is the nurse's specific competence where the care is to be provided in partnership with the patient (Svensk sjuksköterskeförening, 2014). Previous studies have identified several barriers to participation such as staff regarding an older person as lacking in knowledge (Wikström & Emilsson, 2014), staff not listening (Dyrstad, Testad, Aase, & Storm, 2015;Garcia, Harrison, & Goodwin, 2016) lacking empathy, having a paternalistic attitude (Larsson et al, 2011) and deciding on treatment (Aasen et al, 2012).…”
mentioning
confidence: 99%
“…This result is supported by a qualitative study, where a total of 50 staffs were interviewed about autonomy at nursing homes in Sweden. These researchers found that the residents were labelled by the staff as old people who were unable and unwilling to strive for autonomy (Wikström & Emilsson, ). Furthermore, a study regarding QoL in Irish nursing homes showed that the more dependent the resident was on the staff, the less likely they were to have a choice (Murphy, Shea, & Cooney, ).…”
Section: Discussionmentioning
confidence: 99%